2017
DOI: 10.1667/rr14619.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Clinical Signs and Symptoms for Medical Management of Radiation Casualties – 2015 NATO Exercise

Abstract: The utility of early-phase (≤5 days) radiation-induced clinical signs and symptoms (e.g., vomiting, diarrhea, erythema and changes in blood cell counts) was examined for the prediction of later occurring acute radiation syndrome (ARS) severity and the development of medical management strategies. Medical treatment protocols for radiation accident victims (METREPOL) was used to grade ARS severities, which were assigned response categories (RCs). Data on individuals (n = 191) with mild (RC1, n = 45), moderate (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Onset of clinical symptoms such as fever, nausea, vomiting and a decrease in total blood count are important criteria for diagnosing acute radiation syndrome (ARS). Symptomatic changes are useful but can be nonspecific and are not sufficient for determining medical management (4, 5). Cytogenetic observations such as dicentric chromosomes and micronuclei in cultured peripheral blood lymphocytes are the current “gold standards” for assessing radiation biodosimetry (6).…”
Section: Introductionmentioning
confidence: 99%
“…Onset of clinical symptoms such as fever, nausea, vomiting and a decrease in total blood count are important criteria for diagnosing acute radiation syndrome (ARS). Symptomatic changes are useful but can be nonspecific and are not sufficient for determining medical management (4, 5). Cytogenetic observations such as dicentric chromosomes and micronuclei in cultured peripheral blood lymphocytes are the current “gold standards” for assessing radiation biodosimetry (6).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of cases developing ARS and requiring hospitalization were correctly identified by all teams during the exercise. However, determination of severity was particularly challenging for RCs 2 and 3 3 …”
Section: Application Evaluation Via the Exercisementioning
confidence: 99%
“…54 However, a recent NATO exercise and other studies have demonstrated the potential utility of using lymphocyte depletion kinetics for biodosimetry mass screening when early samples are accessible and sufficient resources for processing are available. 55,56 Several software platforms have been developed for use in the point-of-care setting that provide a dose estimate using these existing methodologies. The Biodosimetry Assessment Tool (BAT) is a software platform developed by the Armed Forces Radiobiology Research Institute (AFRRI) that allows dose assessment using clinical symptoms and lymphocyte depletion data.…”
Section: Current State Of the Sciencementioning
confidence: 99%